Kashmiri Women: Vulnerable Section of Society - Irshad, Irshad Ahmad; Dar, Mukhtar Ahmad (International Journal of Social Sciences and Management, 2015)
For last two and half decades tremendous political and social turmoil Jammu and Kashmir is facing by the proxy war between India and Pakistan. This unrest and deteriorated atmosphere has altered the people’s life to the great extent. Their livelihood, health, work culture, education, thinking etc. have altogether changed. Among all the people it is the women of Kashmir, whether Hindu or Muslims, who led a life of great sufferings–psychological disturbance, destitution, poverty, illiteracy, rape, molestation, infertility etc. This paper highlights the problems, miseries, challenges of a weaker sections of society i.e., women who has been confined to child rearing, household duties and have hardly any role in decision making powers. Kashmiri women faced the double burden of a missing husband and social dishonor and isolation of being single women in a conservative society. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12267 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 93-96